METODE KONSTRUKSI RIGID PAVEMENT PADA PROYEK JALAN TOL - Suganda, Raihan; Untari, Yenny (JMTS: Jurnal Mitra Teknik Sipil, 2024)
Road the most widely used means of land transportation on daily basis compared to non-stop air transportation, so volume of vehicles passing through the road must be supported by hardness the exit and entry roads passing through it so that road has a big impact on comfort, welfare and safety for road. Therefore, toll road construction was carried out where implementation planning was carried out using Pd T-14-2003 method which began by determining CBR value, construction of development project from land clearing, soil filling, soil compaction and rigid pavement. The technical formulation and aim is find out how rigid pavement worked thickness layers of rigid pavement has influenceon durability of toll roads by combining explanations regarding the construction process method. This research uses 2 data collection methods with qualitative and quantitative measurement data analysis. Furthermore, conclusion obtained that in the 2017 revised road pavement design manual stated that applicable regulations must be used to determine design life of new pavement. It is important to know according to the CBR provisions, if CBR value is less than 6% then land requires repair, conversely if the CBR value is greater than 6% then there is no need to repair the land. Abstrak Jalan merupakan sarana penting bagi manusia untuk mencapai suatu lokasi yang ingin dijangkau. Dengan adanya perkembangan perbaikan rigid pavement untuk kemajuan struktur jalan baik di metropolitan maupun pedesaan, maka pemerintah terus melakukan peningkatan besar pada jalan-jalan negara. Rigid Pavement merupakan sistem pembuatan jalan yang digunakan pada jalan tol. Keuntungan dari perkerasan kaku juga umurnya yang panjang, visibilitas permukaan pengendaraan yang lebih baik dan perawatan yang lebih sedikit. rumusan dan tujuan penulisan jurnal untuk mengetahui bagaimana teknik pengerjaan rigid pavement jalan tol. Ketebalan pengerjaan rigid pavement memberi pengaruh terhadap ketahanan jalan tol atau terdapat faktor lain di luar keterlibatan pelaksanaan rigid pavement sehingga memadukan penjelasan terkait metode kontruksinya. Hasilnya pengerjaan rigid pavement tentu memberi efek di masa depan dengan ketebalan penggunaan semen beton tidak boleh dilakukan secara suka hati karena perencanaan Perkerasan Jalan (MDPJ) 2017 disebutkan bahwa tebal pelat beton diarahkan dalam perencanaan dengan menggunakan metode Pd T-14-2003. Dimana kontruksi pembangunan jalan tol yang dimulai dari pembersihan lahan – penimbunan tanah- pemadatan tanah – rigid pavement sampai dengan jalan siap pakai dapat direncanakan dengan rencana umur 20-40 tahun juga harus pas dalam penentuan CBR